You are flipping a coin that has a
chance of landing on heads. The value of
follows these rules:
and initially equal 2.
Whenever the coin lands on heads, increases by 1.
Whenever the coin lands on tails, increases by one and then is set to equal (e.g. the first time you flip tails, and will both equal 3, then the second time they will equal 4, etc.)
What is the average number of tails you will flip?
Give your answer to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First, we need to find the probability we flip the first tail. The chance that we flip a head is n 2 n 2 − 1 , meaning that the probability of getting only heads through p turns is n = k ∏ p n 2 n 2 − 1 . After infinite turns, the probability is n = k ∏ ∞ n 2 n 2 − 1 . First, we will use the property n = p ∏ q a n = exp ( ln ( n = p ∏ q a n ) ) = exp ( n = p ∑ q ln ( a n ) ) to make the product into the form n = 2 ∑ ∞ ln ( n 2 n 2 − 1 ) . Using properties of logarithms, this simplifies to exp ( n = 2 ∑ ∞ ( ln ( n + 1 ) + ln ( n − 1 ) − 2 ln ( n ) ) ) . This is a telescoping sum which converges to exp ( ln ( 1 ) − ln ( 2 ) + n → ∞ lim − ln ( n ) + ln ( n + 1 ) ) = exp ( ln ( 2 1 ) ) = 2 1 .
This means that there is a 1 − 2 1 = 2 1 chance we flip at least one tail.
The probability of flipping a second tail once we have flipped the first is n = 3 ∏ ∞ n 2 n 2 − 1 . Using the same strategy as the first, we see this is equal to 3 2 , and more generally, n = k ∏ ∞ n 2 n 2 − 1 = k k − 1 .
This means the probability of getting exactly a tails is ( a + 1 ) ! 1 ⋅ a + 2 a + 1 = ( a + 2 ) ! a + 1 .
By multiplying the previous expression by a and summing it from 0 to ∞ , we get the average number of tails flipped. This is equivalent to:
i = 2 ∑ ∞ ( k ! ( i − 1 ) ( i − 2 ) ) by substituting i = a + 2 to make the denominator i !
By expanding and splitting the sum, we get i = 2 ∑ ∞ i ! i 2 − 3 i = 2 ∑ ∞ ( i − 1 ) ! 1 + 2 k = 2 ∑ ∞ i ! 1
The second and third sums can be quickly evaluated as e − 1 and e − 2 , respectively, leaving only the first sum. Substituting j = i − 1 , the sum becomes ∑ j = 1 ∞ j ! j + 1 . Splitting this apart and evaluating, we get i = 2 ∑ ∞ i ! i 2 − 3 i = 2 ∑ ∞ ( i − 1 ) ! 1 + 2 k = 2 ∑ ∞ i ! 1 = ( e ) + ( e − 1 ) − 3 ( e − 1 ) + 2 ( e − 2 ) = e − 2 = 0 . 7 1 8 2